An Integrated Development Framework for Water Surveillance and Security Management of the Mekong Riverine Peacekeeping Unit, Nong Khai Sector - kiaochaoum, Praepattra; Pajakung, Pichaiyuht (Journal of Thai Ombudsman, 2026)
This study employed a qualitative research design using action research. The objectives were to: (1) analyze the operational situation of officers of the Mekong Riverine Unit in Nong Khai Province using SWOT analysis, and (2) develop strategies for surveillance and water security of the unit. Key informants consisted of 20 officers selected through purposive sampling. Data were collected through semi-structured and in-depth interviews. Data credibility was ensured through triangulation. The data were analyzed using content analysis and thematic analysis. The findings revealed that: 1.The SWOT analysis indicated that the unit’s strengths include personnel expertise, operational efficiency, and strong local collaborative networks. However, key weaknesses lie in limitations of equipment and insufficiently modern support systems, which affect the timely detection and response to threats. Opportunities arise from regional policy support and access to emerging technologies, while threats stem from the increasing complexity of border security issues. The synthesized strategies were categorized into four dimensions: aggressive (SO), defensive (ST), corrective (WO), and preventive (WT) strategies, aiming to systematically enhance operational effectiveness. 2.The strategic development of surveillance and water security systems comprises four key strategies: (1) enhancing capacity through smart technologies, (2) establishing integrated defense mechanisms, (3) strengthening personnel capabilities, and (4) implementing systematic risk management to address security gaps. The implementation of these strategies is expected to modernize surveillance systems, improve responsiveness to complex threats, and sustainably enhance security in the Mekong River border areas. The strategic framework consists of 1 vision, 5 missions, 5 goals, 4 strategies, and 22 supporting measures.